Long-term prognosis, treatment, and outcome of patients with fever of unknown origin in whom no diagnosis was made despite extensive investigation: A questionnaire based study. Issue 25 (June 2018) - Mulders-Manders, Catharina M.; Engwerda, Celeste; Simon, Anna; van der Meer, Jos W.M.; Bleeker-Rovers, Chantal P.
Abstract : Abstract: In 30–50% of patients with fever of unknown origin (IUO) no explanation for the fever can be found. Prognosis and effects of empirical treatment of these patients are largely unknown. With this retrospective, questionnaire based corort study in all unexplained FUO patients in an expert center between 2003 and 2014 we studied mortality and outcome. In 131 of 274 FUO patients, FUO remained unexplained. Ninety-nine of them responded to the long-term follow up questionnaire. Adter a median duration of follow-up of 60 months, spontaneous remission of fever occured in 47.3%. Empirical treatment was effective in 66.7% of patients. Mortality was 6.9%. The cause of death was considered not to be related to the febrile disease in five out of six patients. Ten out of 99 responders reported to have received a final explanation for FUO after evaluation in the expertise center, but this diagnosis could not be confirmed in six cases and was considered to be an unlikely explanation for FUO in four out of six cases. We conclude that mortality in unexplained FUO is low en mostly unrelated to the febrile disease. Spontaneous resolution of fever is common. Empirical treatment prescribed by an expert physician is often effective, but should be avoided untill all diagnostic possibilities have been exhaused. Abstract : Supplemental Digital Content is available in the text